Kemampuan Pemelajar Bahasa Jepang dalam Melafalkan Bunyi Nasal /n/ yang Diikuti Konsonan Bilabial /p/ - Nadia Asnita; Rike Febriyanti (Universitas Gadjah Mada, 2021)
Japanese has a variety of sounds with very interesting features, but these features can cause mispronunciation, especially by foreign students. This study aims to determine the ability of Indonesian Japanese learners to pronounce the nasal consonant /n/ when followed by a bilabial consonant (両唇音) especially /p/. This study uses the descriptive qualitative method, conducted to 10 Japanese language students at Brawijaya University by analyzing their voices using Praat when reciting 3 Japanese sentences which contains [shinpai], [tenpura], and [kanpeki]. We also recorded the voice of Japanese native speakers when reciting the same sentences and use it as a research guide during data analyzing process. From the analysis of pronunciation by native speaker, it is found that the nasal sound produced is a labiodental nasal sound /ɱ/, and there was a stop without vibration when the mouth was closed or in Japanese known as “heisa” (閉鎖) which caused a bilabial popping sound when pronouncing the /p/ sound after the nasal. While for students, it is found that they had several pronunciations similar to the native speaker, but most of them are different pronunciations. The different pronunciations were found in the form of nasal sounds pronounced /n/ only or /m/ only. Some even spell /ng/, and some did not produce pops at the bilabial sound /p/, and other distinct pronunciation were also found in this research.